Peningkatan Literasi Lingkungan Siswa SMP dengan Menggunakan Pendekatan Science Environment Techonology and Society (SETS) - Okti Zulfa Wulandini; Tri Wahyu Agustina; Hadiansah Hadiansah (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
Environmental literacy skills have a major impact on learning success and students' daily lives. This study aims to determine the improvement of environmental literacy by using the SETS approach on ecosystem material. This research is a pre-experimental research. This method is used to analyze the presence or absence of the effect of a treatment with a one group pretest posttest design. The sampling technique used was purposive sampling. The subjects of this study were students of class VII B of Private Junior High School in Bandung City with a total of 30 people. The results showed that based on the N-Gain test, the value of the class using the SETS approach was 0.51 with a moderate category. The existence of this significant difference can be interpreted that there is an increase in environmental literacy by using the SETS approach on ecosystem material.